2021
DOI: 10.1007/s00417-021-05529-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2-RNA in post-mortem samples of human eyes

Abstract: Purpose To detect SARS-CoV-2 RNA in post-mortem human eyes. Ocular symptoms are common in patients with COVID-19. In some cases, they can occur before the onset of respiratory and other symptoms. Accordingly, SARS-CoV-2 RNA has been detected in conjunctival samples and tear film of patients suffering from COVID-19. However, the detection and clinical relevance of intravitreal SARS-CoV-2 RNA still remain unclear due to so far contradictory reports in the literature. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
(43 reference statements)
1
12
0
Order By: Relevance
“…In contrast, a cross-sectional study in Italy reported the presence of viral RNA in the conjunctival swabs of 52 of 91 patients with COVID-19, with a high rate of detection in patients with severe disease 6 . Other cross-sectional studies in China 7 and Brazil 8 , and post-mortem examinations 9,10 also reported viral RNA detection in conjunctival swabs or in the aqueous humour of patients with or without ocular manifestations.…”
mentioning
confidence: 92%
“…In contrast, a cross-sectional study in Italy reported the presence of viral RNA in the conjunctival swabs of 52 of 91 patients with COVID-19, with a high rate of detection in patients with severe disease 6 . Other cross-sectional studies in China 7 and Brazil 8 , and post-mortem examinations 9,10 also reported viral RNA detection in conjunctival swabs or in the aqueous humour of patients with or without ocular manifestations.…”
mentioning
confidence: 92%
“…In hospital settings SARS-CoV-2 can be also transmitted by virus carrying stuff or patients derived respiratory droplets [32] reaching the conjunctiva of patients. In addition, SARS-CoV-2 RNA has been detected post mortem in conjunctival tissues and intravitreal biopsies [33]. Thus the original entry of virus cannot always be ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that the expression of ACE2 is relatively high in the corneal epithelium and suggested that ocular conjunctival inoculation was enough to cause COVID-19 49 , 50 . In addition, various sampling studies identified the presence of SARS-CoV-2 RNA within regions of the visual system, such as the retina, optic nerve, conjunctiva, and vitreous body, in patients with confirmed SARS-CoV-2 diagnoses 51 , 52 . A recent study revealed that the S protein of the novel coronavirus can cross the blood-brain barrier (BBB) 53 .…”
Section: Sars-cov-2 and Neurodegenerative Disordersmentioning
confidence: 99%